Potencial de aplicação do processo foto-fenton/solar como pré-tratamento de efluente da indústria de laticínios - Villa, Ricardo Dalla [UNESP]; Silva, Milady R. Apolinário da [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP] (Sociedade Brasileira de Química, 2007)
Dairy wastewater is characterized by frequent episodes of drastic increases of organic content, giving rise to bulking filamentous bacteria and compromising the biological treatment process. This study reports the reduction of organic content of such wastewater by the application of the solar photo-Fenton process. For a wastewater containing 335, 2627 or 5400 mg C L-1 between 90% and 50% of the organic carbon content were removed after 3.5 h irradiation. The results show that the solar photo-Fenton process can be a good alternative for the abatement of organic content of dairy wastewater, especially in cases of organic content fluctuation, allowing an efficient biological treatment.
Potential application of solar/photo-fenton process for the pre-treatment of wastewater from dairy industry
Keywords: dairy effluent; organic matter; AOP